Option strategies for institutional investment management : a guide for improving portfolio performance - Bookstaber, Richard M.; Clarke, Roger G. (Reading, Mass. : Addison-Wesley Pub. Co., 1983)
This Book will resolve some perplexity, and provide a tool for helping the portfolio manager use options in developing intelligent and informed strategies
Includes index.
Bibliography: p. 160-163.
ucj, 15/01/2019
Loans
Keywords: Options (Finance); Portfolio management